The Social and Environmental Impact of North Coast Jakarta Reclamation in Penjaringan District, 1995-2015 - Windriyanto, Chresida Lestari; Subekti, Slamet (Diponegoro University, 2023)
This article focuses on the dynamics of North Beach reclamation in Penjaringan sub-district. Reclamation is an activity that is considered beneficial for improving the use of land resources. This study uses the historical method to explain the policy underpinning the implementation of reclamation and the impact of reclamation on social life in Penjaringan Sub-district. Reclamation development has been planned since Presidential Decree (Keppres) No. 52/1995 on Reclamation of the North Coast of Jakarta was issued by the New Order government. In its implementation, the policy that led to the implementation of reclamation had adverse impacts in both environmental and social aspects. This was caused by overlapping policies that only benefited the developers. In addition, the implementation of reclamation as an implementation of government policy did not pay attention to the social and environmental impacts for the surrounding community.